Conflict as Sciential Object - Čiuladienė, Gražina (Acta Paedagogica Vilnensia, 2005)
Psychological conception of conflict was formed by several trends: psychoanalysis, behaviourism, cognitive. There separate thesis could be used to define conflict as integrated 3 levels (cognitive, affective and action) phenomenon. Although it could be used the same definition for conflicts occurred in education context, there are same specific means of it in educology. Firstly it is the form and the result of teachers’ behaviour. Secondly, the misbehaviour of pupils is named as conflict. Lastly, conflict as unavoidable appearance, is the indicator of teachers’ conflict competence. Conflict between teacher and pupils was usual in traditional school, but in there are justified only constructive conflicts in democratic school.
Keywords: education; school; conflict; psychological conception